Lipidoma e expressão gênica de oócitos obtidos de doadoras de genótipos leiteiros bos taurus, Bos indicus e Bos taurus/indicus - Lopes, Asafe Costa (2022)
The use of in vitro embryo production (IVP) for dairy breeds has increased significantly in recent years. Differences in the number and developmental potential of oocytes between female taurine (Bos taurus) and zebu (Bos indicus) breeds affect the efficiency and economic viability of IVP. The aim of this study was evaluate the lipid profile and content, as well as the mRNA abundance of genes involved in lipid metabolism, in oocytes recovered from the following dairy breeds: Gir (Bos indicus), Holstein (Bos taurus), and their crossbreeds (1/2 Holstein × 1/2 Gir). Cumulus-oocyte complexes (COCs) were recovered by follicular aspiration, and immature COCs were processed to separate oocytes from cumulus cells, and then subjected to semi- quantitative evaluation of oocyte cytoplasmic lipid droplets using Sudan Black B staining, analysis of the lipid profile through mass spectrometry using multiple reaction monitoring, and abundance analysis of the mRNA of genes involved in lipid metabolism through real-time polymerase chain reaction. To analyze gene expression in oocytes matured in vitro, immature COCs were subjected to in vitro maturation for 24 h. Cytoplasmic lipid content was found to be similar in immature oocytes obtained from Gir, Holstein, and crossbred donors. The concentrations of triacylglycerols, cholesteryl ester, diacylglycerol, phosphatidylinositol, and ceramide did not vary between breeds. The total abundance of phosphatidylcholine was higher in oocytes from Gir donors than in those from Holsteins and crossbreeds, and the abundance of sphingomyelin and phosphatidylethanolamine was higher in Gir oocytes than in Holstein oocytes, whereas that of crossbreeds did not differ from that of the other breeds. Partial least squares discriminant analysis showed stratification between breeds in terms of membrane lipids, indicating that breed had an effect on the profile of membrane lipids in oocytes, and 19 lipid species were determined to be different between breeds using analysis of variance. The mRNA levels of SPHK2, ACSL3A, and CPT2 were higher in immature oocytes from Gir and crossbred donors, whereas the abundance of LRAT mRNA was higher in immature oocytes from Gir donors than in Holstein oocytes, with oocytes from crossbred donors having an intermediate LRAT mRNA abundance. The expression levels of ATX, CPT1B, ACADL, and CD36 were higher in immature Gir oocytes than in Holstein oocytes. In relation to in vitro- matured oocytes, the abundance of ATX, CPT1B, and CD36 was higher in oocytes from Gir and crossbred cows than in those from Holstein cows, whereas the abundance of LRAT and ACADL mRNA was higher in oocytes from Gir cows than in those from Holstein cows, with oocytes from crossbred cows having an intermediate abundance. Furthermore, the expression of SPHK1 and CPT1A was higher in Gir cows than in Holstein cows. Lipid and transcriptional profiles showed clear differences between purebred, Gir, and Holstein oocytes. The higher concentration of membrane lipids in Gir oocytes, associated with the greater abundance of genes that metabolize these lipids, indicated that there are metabolic conditions that particularly favor the generation of important chemical messengers for oocyte development in Gir cows, as compared to that in Holstein cows.